Transforming initial teacher education - Abbott, Ian, 1955- (Routledge, 2019)
"Tracing the development of Initial Teacher Education (ITE) since the large scale expansion of the teaching professional after the Second World War to the present day, this book explores the changing nature of teacher education. It considers the growth of the 'teaching industry' and addresses key issues including the return to an apprentice model, the growing importance of schools in ITE and the continuing decline in the role played by Higher Education. The book sets these changes in the broader international context to consider the future of teacher education and the changing nature of teaching"--